Recurrent malignant proliferating trichilemmal tumour of the scalp: a case report. Issue 3 (1st June 2015) - Reddy, Lohith G.; Jayakumar, Vijetha; Rajan, Sudhan; Bilimagga, Ramesh S.; Priyadarshini, V.; Anbumani, Surega
Abstract Introduction Proliferating trichilemmal tumour (PTT) is a benign tumour originating from the outer root sheath of a hair follicle. In rare instances, malignant transformation has been reported, evidenced by regional or distant metastases. Malignant transformation of PTT is often confused with squamous cell carcinoma. PTT usually occur as a solitary lesion on the scalp. It was first described as a proliferating epidermoid cyst by Wilson-Jones in 1966. Case description A female patient presented with a growing lesion on scalp in the right parietal region. She had already undergone excision for the same 8 months ago. The cyst was surgically removed and scalp was treated with electron therapy using a field dimension of 8×8 cm in 2011. Now, the patient is disease free with good quality of life. Conclusion Oncologists can consider electron therapy in management of PTT. This can improve cosmesis and quality of life of these patients.